Conflict and Cooperation on South Asia's International Rivers : A Legal Perspective - Salman, Salman M.A.; Uprety, Kishor (Washington, DC: World Bank, 2013)
The book analyzes five major bilateral treaty regimes on the South Asian subcontinent: between India and Bangladesh for the Ganges River; between India and Nepal for the Kosi, Gandaki, and Mahakali rivers; and, between India and Pakistan for the Indus River. It explains the background, and legal regimes of these international rivers in the context of the serious challenges to the water resources of the subcontinent, posed by significant population increases, urbanization, industrialization, and environmental degradation. International lawyers, and natural resource specialists will find this book to be useful and informative.